Synthesis, electronic structure and reactivity of rhodium(I) and iridium(I) bis(imino)acenaphthene complexes - Bezuidenhout, Daniela I. (University of Pretoria, 2023)
Thesis (PhD (Chemistry))--University of Pretoria, 2022.